2005
DOI: 10.2310/6350.2005.31246
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double‐Blind Comparison of the Efficacy of Two Hyaluronic Acid Derivatives, Restylane Perlane and Hylaform, in the Treatment of Nasolabial Folds

Abstract: Restylane Perlane provides a more durable esthetic improvement than Hylaform and offers acceptable tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 11 publications
1
82
0
5
Order By: Relevance
“…Wrinkle grading systems of varying complexity have been validated for reproducibility and reliability and are used for assessing the efficacy of treatments such as botulinum toxin A injections 5,6 and hormone replacement therapy 7 and for the classification of facial wrinkles. 8 Other examples include the Wrinkle Severity Rating Scale (WSRS), which is a 5-grade assessment system of labial folds that was validated 9 and then applied in two studies to distinguish between two treatments for facial soft tissue augmentation, 10,11 and the Lemperle scale, which was used in a study (abstract presented in AAD, 2006, 12 to compare two treatments for nasolabial fold correction.…”
mentioning
confidence: 99%
“…Wrinkle grading systems of varying complexity have been validated for reproducibility and reliability and are used for assessing the efficacy of treatments such as botulinum toxin A injections 5,6 and hormone replacement therapy 7 and for the classification of facial wrinkles. 8 Other examples include the Wrinkle Severity Rating Scale (WSRS), which is a 5-grade assessment system of labial folds that was validated 9 and then applied in two studies to distinguish between two treatments for facial soft tissue augmentation, 10,11 and the Lemperle scale, which was used in a study (abstract presented in AAD, 2006, 12 to compare two treatments for nasolabial fold correction.…”
mentioning
confidence: 99%
“…This could be a very useful value add on in a dental practice as these can prove to be very safe and effective instruments for rejuvenation of the peri-oral area besides improving the smile of the patient. A number of studies have been performed to evaluate the longevity and safety of fillers [2][3][4]. Ideal filler should be sterile, biodegradable, non-pyrogenic, viscoelastic, clear, colorless, homogenous gel filler.…”
Section: Discussionmentioning
confidence: 99%
“…NLF's extend from the side of the nose to the corner of the mouth and are often exaggerated early in the aging process [2]. There are a vast variety of hyaluronic acid fillers available in the market today for the same [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment-related adverse events tended to occur more frequently on the non-animal-stabilized filler treated site Treatment related [74] Prospective study (n = 248), 6 months follow-up Short-term complications were observed in more than half of the subjects. In 2 cases treatment of the adverse event was necessary Treatment related [75] Prospective study (n = 439), 6 months follow-up ‡, §…”
Section: Hyaluronic Acid (Cross-linked)mentioning
confidence: 99%